EFFORTS TO INCREASE STUDENT LEARNING INTEREST BY USING COOPERATIVE LEARNING MODEL BAMBOO DANCE TYPE ON BASIC COMPETENCIES OF PANCASILA AS THE BASIS OF PKN SUBJECTS IN GRADE VII SMP NEGERI 1 SIMANGUMBAN T.A 2017/2018 - Morris Gultom (Jurnal Sabilarrasyad, 2020)
The problem faced by the teacher was the problem of the low interest in student learning in Civics subjects in Class VIII of SMP Negeri 1 Simangumban. This study aims to determine whether using the cooperative learning model of the bamboo dance type can improve student learning interest in Civics in Class VIII of SMP Negeri 1 Simangumban in the 2017/2018 academic year. This type of research is "Classroom Action Research", using a cooperative learning model of the bamboo dance type. This study aims to determine that using the cooperative learning model of the bamboo dance type can improve student learning interest on the subject of Pancasila as the State Foundation in Class VIII of SMP Negeri 1 Simangumban Academic Year 2017/2018. This study consisted of 2 cycles, cycle I and cycle II, each of which had 2 meetings. At each meeting the researcher carried out learning observations of students, to determine the level of student interest in learning. Based on the results of observations made by the author with Class VIII teachers of SMP Negeri 1 Simangumban which was conducted on 30 students, there were 24 students (80%) who had less interest in learning and 6 students (20%) who had sufficient interest. Then in the first cycle, it has an average value of 44 (55%), while in the second cycle it is 69 (87%). Based on the results of the research from the cycle I test with cycle II, there was a significant increase, thus it can be concluded that by applying the cooperative learning model of the bamboo dance type, it could improve student learning interest in Civics subjects, the subject of Pancasila as the State Foundation in Class VIII of SMP Negeri 1 Simangumban Academic Year 2017/2018.